Respuesta :

1)

Answer:

Explanation:

The given function is

f(x) = x^2 - 2x - 3

The first step is to graph the function. We would substitute values of x into the function and find corresponding values of y or f(x). We have

For x = - 1, y = (- 1)^2 - 2(- 1) - 3 = 1 + 2 - 3 = 0

For x = 0, y = (0)^2 - 2(0) - 3 = 0 + 0 - 3 = - 3

For x = 1, y = (1)^2 - 2(1) - 3 = 1 - 2 - 3 = - 4

The points to be plottted on the ggraph are

(- 1, 0)

(0, - 3)

(1, - 4)

We would plot these point on the graph as shown below

The axis of symmetry is the vertical line that divides the graph into two equal hv

Ver imagen EdinB68853
ACCESS MORE